Fiber-based BN aerogels for efficient and cross-scale removals of microorganisms and pollutants in water. Issue 11 (1st June 2021) - Chen, Zhiwei; Zeng, Lula; Xiang, Shuo; Deng, Yuxian; Jiang, Kang; Han, Guangze; Zhang, Shiguo; Ge, Xingyi; Weng, Qunhong
Abstract: Water purification is an important issue in our daily life. Various pollutants, from micrometer-sized microorganisms to molecular- or atomic-sized pollutants, need to be efficiently removed from water. Unlike traditional cascade-stage techniques, we report a one-step water purification method based on a ceramic aerogel composed of porous BN fibers, which realizes >99% Microcystis and >98% E. coli cell removals from water and high-capacity adsorptions of pesticide, oils, organic compounds, metal ions, etc. The adsorption capacities for metal ions are about one order of magnitude higher than those achieved by the reported porous/activated carbons. Our studies show the importance of the unique hierarchical structure of the BN aerogel to realize remarkable water purification performances; micrometer-sized pores constructed by high-dense fibers, the porous structures and rich surface functional groups of the BN fibers all contribute to the efficient removals of different types of the pollutants. These results suggest the potential applications of the BN aerogels toward one-step and comprehensive water purifications. Graphical abstract: Image 1 Highlights: Aerogels made of dense BN fibers are highly efficient for removals of microorganisms and pollutants in water. The unique hierarchical structure of BN aerogel is critical to realize simultaneous removals of cross-scale pollutants.